Modern ecocritical movements in pop-culture: Songs as a medium of environmental concerns about urbanization in 1970s American radio hits - Arum, Dewi Sekar; Zulyeno, Bastian (EduLite: Journal of English Education, Literature and Culture, 2025)
As an interdisciplinary study, ecocriticism has significantly influenced the recognition of ecological concerns within the cultural phenomena of literature, including popular narratives such as songs. The use of poetic narratives in songs to address ecological issues and agendas has garnered expansive interest in the social marketplace, driven by the interplay of natural, cultural, and political dialogues. This study employed Roland Barthes’s semiotic perspective and Greg Garrard’s ecocritical theory to analyze environmental themes in the lyrics of three songs: “Big Yellow Taxi” by Joni Mitchell, “Ain’t It a Sad Thing” by Richard Dean Taylor, and “Apeman” by The Kinks. These songs, through their literary narratives, explored key ecocritical concepts such as pollution, animals, dwelling, and the earth, highlighting the impacts of urban life on ecological systems. Using a qualitative approach to interpret the data, the analysis reveals that, as early as the 1970s, environmental awareness of ecological damage was a recognized global concern. The lyrics serve as a medium of social critique, emphasizing the importance of harmony between humans and nature. Through their representation of the human-nature relationship, the songs contribute to an understanding of the interconnection between civilization and sustainability, promoting environmental ethics in managing the natural world. By projecting ecological issues within their narratives, the songs stimulate ecological awareness and underscore the urgency of addressing environmental challenges.